1999
DOI: 10.1101/lm.6.4.347
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Ablation of Auditory Cortex in Mongolian Gerbil Affects Discrimination of Frequency Modulated Tones but not of Pure Tones

Abstract: This study examines the role of auditory cortex in the Mongolian gerbil in differential conditioning to pure tones and to linearly frequency-modulated (FM) tones by analyzing the effects of bilateral auditory cortex ablation. Learning behavior and performance were studied in a GO/NO-GO task aiming at avoidance of a mild foot shock by crossing a hurdle in a two-way shuttle box. Hurdle crossing as the conditioned response to the reinforced stimulus (CR+), as false alarm in response to the unreinforced stimulus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(34 citation statements)
references
References 87 publications
5
28
0
1
Order By: Relevance
“…has been shown that bilateral lesions of auditory cortical areas impair frequency-modulated tone discrimination but have little effect on pure tone discrimination (Ohl, Wetzel, Wagner, Rech, & Scheich, 1999). Thus, neurons in primary or secondary auditory cortices may provide the neural substrates for parsing co-occurring sounds based on frequency periodicity, and they probably contribute to the ERP responses elicited by perceptually segregated sounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…has been shown that bilateral lesions of auditory cortical areas impair frequency-modulated tone discrimination but have little effect on pure tone discrimination (Ohl, Wetzel, Wagner, Rech, & Scheich, 1999). Thus, neurons in primary or secondary auditory cortices may provide the neural substrates for parsing co-occurring sounds based on frequency periodicity, and they probably contribute to the ERP responses elicited by perceptually segregated sounds.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from single-cell recordings in nonhuman primates (for a review, see Rauschecker, 1997) and neuromagnetic recordings in humans (Langner, Sams, Heil, & Schulze, 1997) suggests that frequency periodicity is represented within the primary or secondary auditory cortices, or both (Langner et al, 1997). In animals, it has been shown that bilateral lesions of auditory cortical areas impair frequency-modulated tone discrimination but have little effect on pure tone discrimination (Ohl, Wetzel, Wagner, Rech, & Scheich, 1999). Thus, neurons in primary or secondary auditory cortices may provide the neural substrates for parsing co-occurring sounds based on frequency periodicity, and they probably contribute to the ERP responses elicited by perceptually segregated sounds.…”
Section: Discussionmentioning
confidence: 99%
“…With such differences in the ability to manipulate inactivation spatially and temporally, each method has its own advantages and limitations ( Table 1 ). Timescale itself is a significant factor since the duration of loss of AC function ( Figure 2 ) shapes the magnitude of the observed deficit: in many cases, performance on a task continues to evolve for a long time after the inactivation, with most severe impairments occurring in the short term [ 4. , 5.…”
Section: Challenges In Defining Auditory Cortex Functionmentioning
confidence: 99%
“…In most cases, AC inactivation does not impact the performance of tasks requiring discrimination of simple features. Severe deficits are reported only when reversible inactivation methods are used, that likely target the whole AC [ 24 , 43 ] or for a limited period following a lesion [ 4. , 5.…”
Section: Ac’s Role In Auditory Behavioursmentioning
confidence: 99%
“…Previous studies indicate that the auditory cortex may play an important role in the processing of these time-varying features of sounds. For example, gerbils with total bilateral ablation of the auditory cortex are no longer capable of discriminating the direction of change of frequency-modulated (FM) sounds, even though their capacity to discriminate pure tone stimuli remains intact after such ablation (Ohl, Wetzel, Wagner, Rech, & Scheich, 1999; Wetzel, Ohl, Wagner, & Scheich, 1998). Similarly, electrophysiological studies performed in various species indicate that auditory cortical neurons are highly sensitive to FM sounds.…”
mentioning
confidence: 99%